Entangled in the Continuum of Violence: How do Women Experience War? - Korać, Srđan T. (Review of international affairs, 2022)
The paper illuminates several issues that arise from the lack of or extensive marginalisation of the female wartime experiences as a relevant debate topic in International Relations (IR) of the day. The analysis is positioned in feminist IR theories and gender studies of war and centres around the notion of continuum of violence as an optimal conceptual tool to embrace the complexities of interactions between women’s agency in war and their pervasive victimisation. By employing the concept of continuum of violence, two intertwined planes of female war experiences are examined: the experiences of knowing war and the experiences of doing war. The author concludes that, despite the representational power of the corporate and social media in conveying images of reality to an everwidening public, wartime experiences of women continue to be blurred and devalued in contrast to glorification of masculine ideal of male hero. Women’s experiences of war are officially acknowledged only if they fit the patriarchal order and dominant narratives on the state in international relations, not if they challenge gendered discursive practices. The gender stereotyping of women as “natural” non-combatants reproduces marginalisation of female experiences in doing war as female soldiers are either silenced after conflict or labelled as deviants.